Functionalization Strategies of MXene Architectures for Electrochemical Energy Storage Applications - Shude Liu; Huilin Zhang; Jieming Chen; Xue Peng; Yafei Chai; Xian Shao; Yi He; Xiaoqiang Wang; Bin Ding (Energies)
MXene, an emerging class of two-dimensional materials, has garnered significant attention in electrochemical energy storage applications due to its high specific surface area, tunable surface functional groups, excellent electrical conductivity, and mechanical stability. However, their practical application in energy storage devices remains challenged by issues such as the stacking of their layered structure, surface degradation, and limited ion diffusion properties. Functionalization has emerged as a key strategy to enhance the performance of MXene materials. By modulating surface functional groups, doping with various elements, and integrating with other materials, researchers have significantly improved the electrical conductivity, chemical stability, ion transport properties, and mechanical strength of MXenes. This review provides a comprehensive overview of MXene materials, categorizing them and highlighting their advantages in electrochemical energy storage applications. It also examines recent advancements in MXene preparation and optimized synthesis strategies. In-depth discussions are presented on the functionalization of MXenes and their applications in energy storage devices, including supercapacitors, lithium-ion batteries, and sodium-ion batteries. Finally, the review concludes with a summary of the practical applications of MXenes and explores future research directions, aiming to guide further developments in the energy storage field.